FLOWERS OF CUCURBITA MAXIMA DUCH. AS A SOURCE OF ANTIOXIDANTS AND PROSPECTS OF THEIR USE IN FOOD - A. F. Bukharov; N. V. Stepaniuc; A. R. Bukharova; M. I. Ivanova (Овощи России, 2019)
The bright yellow flowers are edible pumpkin - a good source of antioxidant compounds . The maximum level of  hydroxycinnamic acids  noted  in  the  half  parted flower . The remaining components were studied at the maximum in the unopened buds .  By the beginning of the flower opens flavonoids and carotenoids concentration  decreased gradually .  In  full disclosure of  the flower phase of the content of these components increases again, but it did not reach the initial level. A similar, but  less  pronounced  trend  of  the  observed and chlorophyll .